On a Coupled Cahn–Hilliard System for Copolymer/Homopolymer Mixtures (Journal of Mathematical Study, 2022)
Our aim in this paper is to study a coupled Cahn–Hilliard system forcopolymer/homopolymer mixtures. We prove the existence, uniqueness and regularity of solutions. We then prove the existence of finite dimensional global attractors.
Keywords: Coupled Cahn–Hilliard system; well-posedness; finite dimensional global attractors.